Unbundling of electricity transmission system operators in Germany: An experience report - Gert Brunekreeft; Mika Goto; Roland Meyer; Masahiro Maruyama; Toru Hattori (Jacobs University Bremen, Bremen Energy Research (BER), 2014)
The purpose of this research is to evaluate the impact of vertical unbundling on German electric utilities. Our research mainly relies on in-depth interviews with sector-experts from the German utilities. We will discuss both short-term changes and the long-term impact on competition in the electricity market as well as the impact on costs and security of supply. Overall, we have two main conclusions. First, the major step in the unbundling process is from "lean legal unbundling" to "fat legal unbundling"; additional steps beyond that are small, both in benefits and in costs. Second, the benefits of unbundling in terms of increased competition do not come for free: unbundling is costly and it is important to balance cost and benefits in the reform process.
Keywords: L43; L51; L94; 330; electricity; unbundling; regulation; competition policy